1987
DOI: 10.3382/ps.0661714
|View full text |Cite
|
Sign up to set email alerts
|

Ingestive Behavior of Meat and Egg-Type Chickens: Equal Sensitivity to Naloxone

Abstract: The efficacy of the opioid antagonist naloxone in attenuating ingestive behavior in stocks of chickens genetically selected for either meat (Rock-Cornish, RC) or egg production (Single-Comb White Leghorn, SCWL) was investigated. Because the stocks differ markedly in growth rate, two experiments were conducted to compare RC and SCWL cockerels at similar body weights and at the same age. Birds were injected intramuscularly with either isotonic saline or naloxone HCl at a dose of 5 mg/kg body weight. Food and wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

1989
1989
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
(36 reference statements)
2
2
0
Order By: Relevance
“…The reduced water intake noted in those treatments where naloxone was administered is in agreement with previous work in the chicken (McCormack and Denbow, 1987) although All was not administered in those studies. Studies using rats as the experimental animal have shown attenuation of drinking induced by AH by naloxone at a 5 mg/kg BW dosage (Summy-Long et al, 1981a).…”
Section: Table 1 Effects Of Injection Of Angiotensin II (All) 1 Nalsupporting
confidence: 90%
See 3 more Smart Citations
“…The reduced water intake noted in those treatments where naloxone was administered is in agreement with previous work in the chicken (McCormack and Denbow, 1987) although All was not administered in those studies. Studies using rats as the experimental animal have shown attenuation of drinking induced by AH by naloxone at a 5 mg/kg BW dosage (Summy-Long et al, 1981a).…”
Section: Table 1 Effects Of Injection Of Angiotensin II (All) 1 Nalsupporting
confidence: 90%
“…Injection of AH alone increased water intake of chicks to 12 h when compared with the saline-injected controls, but the effects were no longer evident at 24 h. Naltrexone injection did not have any effect on the Allinduced increase in water intake. The reduced feed intake to 4 h noted with the opioid antagonists has been documented previously in domestic fowl (McCormack and Denbow, 1987). Cumulative food intake was reduced in the AH, naltrexone, and naloxone groups at 1 h when compared with the control group (Table 2).…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations